Clinical Assessment of the Accuracy of ICP Non-invasive Measurement - Ragauskas, A.; Šunokas, R.; Žakelis, R.; Matijošaitis, V. (Elektronika ir Elektrotechnika, 2010)
According to the invasive ICP monitoring technologies disadvantages and that uncertainties of the best solid state invasive absolute ICP (aICP) sensors are within the limits from 4.2 mmHg up to 19.2 mmHg, a new innovative method for a non-invasive absolute ICP value measurement without the individual calibration problem has been created in Telematics Scientific Laboratory of Kaunas Univer-sity of Technology. In order to evaluate the accuracy of new non-invasive absolute ICP value meter clinical study of simultaneous inva-sive and non-invasive aICP measurements will be performed on neurological patients comparing aICP measured non-invasively with eICP measured with lumbar puncture, which is considered „golden standard“ and every new method must be compared with it.